Growth of plants under different temperature conditions: are the Antarctic plants unique - Matvieieva, N.; Chapkevich, S.; Drobot, K.; Duplij, V. (Ukrainian Antarctic Journal, 2012)
The influence of low (+3 °C) and high (+36 °C) temperatures on the growth rate and polyfructan accumulation in the plants of Warnstorfia fontinaliopsis (Müll. Hal.) Ochyra and duckweed (Lemna minor L.) has been investigated. There was the similar decreasing of plants weight growth for Antarctic moss W. fontinaliopsis and for the duckweed as a result of low or high temperature treatment. Short period (2 days) of cultivation under the +3 °C had no effect on the weight increase of W. fontinaliopsis. Under these conditions changes in weight increment Δm = 0,023 g was the same as for control plants that were grown at +24 °C. Longer cultivation at low temperatures (15 and 30 days) resulted in the significant (2.01 and 2.33 times respectively) decreasing of moss weight gain. In the last case weight increase was only 0.01 g. Duckweed plants were more susceptible to prolonged exposure (30 days) of low temperature. Culturing in such conditions led to 7 times reduction of weight increment comparatively to weight increase of untreated L. minor plants. W. fontinaliopsis, in contrast, shows only 2.3 times reduction of weight increase. The differences in accumulation of polyfructans after low or high temperature treatment of W. fontinaliopsis and L. minor were shown. Increasing of polyfructan content under the stressful conditions has been observed only in duckweed plants. Probably, moss W. fontinaliopsis and L. minor have different protective mechanisms against stressful temperatures.